HUBUNGAN STATUS PEKERJAAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS KAWANGKOAN - Timporok, Anggania G.A; Wowor, Pemsi M; Rompas, Sefti (Universitas Sam Ratulangi, 2018)
Abstract : breast milk is the best food for the baby's growth. Nutrient found in breast milk isvery complete and very beneficial to the baby. ASI is Exclusive breast feeding to baby food anddrinks without an escort which started since the new baby is born. Purpose:of this research isto know the relation of maternal employment status with exclusive breast feeding. Researchmethods: method using descriptive analytic with cross sectional study approach. The sampleuses the total sampling method i.e. 72 mother while giving exclusive breast milk at work-areaClinics Kawangkoan. This research use questionnaire instruments and data analysis using Chi-Square test Results: based on Chi-square test results showed the existence of a relationshipbetween the two variables with the value p = 0.000 less than Î± = 0.05. The conclusion: Thereis significant correlation between occupational status with the exclusive breastfeeding working areaof Kawangkoan public health.Keyword: Occupational status, Exclusive breast feedingAbstrak : ASI merupakan makanan terbaik bagi tumbuh kembang bayi. Kandungan gizi yangterdapat dalam ASI sangat sempurna dan sangat bermanfaat bagi bayi. Asi eksklusif adalahpemberian ASI (air susu ibu) sedini mungkin setelah persalinan sampai bayi berumur 6 bulan.Tujuan penelitian ini untuk mengetahui hubungan status pekerjaan ibu dengan pemberian ASIeksklusif. Metode penelitian menggunakan metode deskriptif analitik dengan pendekatancross sectional study. Sampel Penelitian ini menggunakan instrumen kuesioner dan analisa datamenggunakan uji Chi-Square. Hasil penelitian berdasarkan uji Chi-square menunjukan hasiladanya hubungan antara kedua variabel dengan nilai p=0,000 kurang dari Î±=0,05. Kesimpulandari penelitian ini adalah ada hubungan anatar status pekerjaan ibu dengan pemeberian ASIeksklusif di wilayah kerja Puskesmas Kawangkoan.Kata Kunci: Status Pekerjaan Ibu, ASI Eksklusif.Â